Dissecting the genetic architecture of quantitative traits in common bean (Phaseolus vulgaris L.): response to root-knot nematode infection and seed morphology - Giordani, Willian (2021)
Common bean (Phaseolus vulgaris L.) is the leading legume grain for human consumption and a staple food in many regions of the world. Since most common bean is produced in the tropics under low-input systems, phytosanitary issues often severely impact yield. Among the principal Phaseolus spp. pathogens, root-knot nematodes (RKN), particularly Meloidogyne incognita, are probably the most widespread and damaging. Despite their importance, effective control is still not available and due to the imprecision and slowness of the traditional phenotyping procedures, common bean breeding programs have faced huge challenges in developing routine nematode resistance screening. Likewise, another complex task tackled by bean breeders is the need to focus on specific traits to satisfy the requirements of farmers, industry and end consumers. This applies to seed size, weight and shape. With the advent of low-cost next-generation sequencing, genetic mapping approaches such as quantitative trait loci (QTL) analysis and genome-wide association studies (GWAS) have proved to be remarkable approaches to quantitative trait genetic architecture studies. The Laboratory of Molecular Genetics of Crop Plants has, as one of its main research activities, the development of fundamental studies on diversity and genetic mapping in P. vulgaris. This has entailed developing a core collection panel of 180 accessions, genotyped using 10,362 SNPs and recommended for use in association mapping. In this thesis, two distinct investigations are described, each detailing an individual study, converging to achieve the overarching goal of expanding the comprehension about the genetic factors underlying common bean traits. The first study combines two genetic mapping approaches (GWAS and QTL mapping), bioinformatics and histochemical analysis to dissect the complex genetic architecture of the common bean response to RKN. GWAS identified independent genomic regions associated with the number of RKN egg masses (Pv06, Pv07, Pv08 and Pv11) and the root-galling index (Pv01, Pv02, Pv05 and Pv10), and several genes were highlighted as prominent candidates in common bean response to the pathogen. In the second study, GWAS and high-throughput image-based phenotyping were applied to pinpoint loci associated with common bean seed morphology. Seven marker-trait associations, explaining a considerable amount of phenotypic variation, were discovered for seed length, width, projected area, perimeter and circularity in four distinct genomic regions of chromosomes Pv02, Pv08 and Pv11, and at least 13 genes were considered promising candidates for regulating seed morphology. From a practical standpoint, the studies documented in this thesis provide SNP markers that may help breeders in marker-assisted selection, and the genes suggested herein are promising candidates for functional analysis in common bean and eventually other related crops.